Dual-labeling of ubiquitin proteins by chemoselective reactions for sensing UCH-L3. Issue 6 (22nd April 2016) - Li, Lei; Zhang, Si-Yu; Li, Yan-Mei; Chen, Yong-Xiang
Abstract : SUMO-fused and intein-fused protein expression systems have been combined to prepare a dual-color labeled ubiquitin sensor for detecting UCH-L3's activity. Abstract : A site-specific dual-color labeled ubiquitin for sensing deubiquitinase's activity was prepared by consecutively using chemoselective native chemical ligation reactions in a facile and efficient way. The prepared sensor was applied to establish a sensitive FRET-based assay for UCH-L3.